First report of Acute Oak Decline symptoms in the Himalayas– A tree disease causing rapid death of Himalayan Banj Oak (Quercus leucotrichophora) in Uttarakhand, India - Chandran, M.; Verma, A.K.; Singh, V.K.; Kumar, N. (Indian Forester, 2024)
No Abstract.